Predictors of psychological distress and well-being in a sample of Australian undergraduate students - Bore, Miles; Pittolo, Chris; Kirby, Dianne; Dluzewska, Teresa; Marlin, Stuart (Higher education research and development, 2016)
Previous research has found university students report higher levels of psychological distress compared to the general population. Our aim was to investigate the degree to which personality and contextual factors predict psychological distress and well-being in students over the course of a semester. We also examined whether resilience-building skills, such as positive self-talk, mindfulness meditation and self-management, included in a first-year psychology subject, might reduce distress and improve well-being. Undergraduate first-year students (n = 150) completed a battery of questionnaires in week three (Time 1; n = 150) and week 10 (Time 2; n = 53) of semester. At both times students reported high levels of psychological distress, as measured by the K10, the General Health Questionnaire and the Brief Symptom Inventory, and low levels of psychological well-being, as measured by the Warwick Edinburgh Mental Well-Being Scale. Students exposed to resilience-building skills embedded in a subject (n = 24) were no less distressed at Time 2 than those not enrolled in that subject (n = 29). The personality traits of emotional resilience (vs. reactivity) and bounce-back resilience measured at Time 1 were the only significant predictors of psychological distress and well-being measured at Time 2. Students with high emotional and bounce-back resilience had lower psychological distress and higher well-being scores. Future research could consider development and trial of a full semester university subject designed to improve students' resilience knowledge and skills.